An ANALYSIS OF STUDENTS’ ABILITY IN APPLYING SIMPLE PAST TENSE IN RECOUNT TEXT AT SMP N 1 PANGARIBUAN - Herawati Pakpahan (English Language Teaching Prima Journal (ELT), 2020)
Abstract Recount text is a kind of text in english that tell about a story, actions or event which use simple past tense. Meanwhile, simple past tense is an event that happen in past, the characteristic of simple past tense is using verb 2. Students’ability are a condition to determine students skill in applying simple past tense in recount tense. The aim of this research were to analyzed the students’ ability in applying simple past tense in recount text. This research performed at eight grade in Smp N 1 Pangaribuan. Researcher used qualitative research designs. The data was collected by test, and questionnaire. Based on students test result, the average score of 20 students at eight grade in Smp N 1 Pangaribuan was 55,4. The data from questionnaire showed that 11 from 20 students couldn’t remember the pattern of simple past tense. 12 from 20 students didn’t know about simple past tense or couldn’t make sentence in simple past form. 15 from 20 students couldn’t remember verb in simple past, 12 from 20 students thought that recount text was difficult. And 17 from 20 students couldn’t write recount text correctly. Keywords : Students’ Ability, Simple Past Tense, Recount Text